Spectroscopic studies of magnetic cataclysmic variables - Van der Heyden, Kurt Josias (Department of Astronomy, 2023)
In this thesis I present the results of optical spectroscopic analyses of four Polars and the spectra of five new systems. The results of four candidate magnetic cataclysmic variables, which were selected from the ROSAT Bright Survey, are also presented. Time resolved spectra are used for the dual purpose of conducting Doppler tomographical studies and searching for any evidence of cyclotron beaming. The first five chapters are introductory and background sections, including a review of all individual objects with magnetic field strengths determined by cyclotron spectroscopy. In Chapter 6 I discuss the observations, data reduction and analysis techniques while the results of individual objects are presented in Chapter 7. Results are presented for the two Polars HU Aqr and QS Tel, which were selected as test objects to confirm the techniques of Doppler tomography and cyclotron spectroscopy, respectively. Doppler maps, similar to those previously obtained, are produced for HU Aqr. Two cyclotron humps are also detected in the HU Aqr spectra corresponding to a magnetic field of 39 MG, again similar to values quoted in the literature. A complex cyclotron spectrum for QS Tel indicates that the second magnetic pole is more dominant than in previous studies. Spectra are presented for the new Polars RX J1313-32, RX J1141-64, RX J1610+03, RX J0153-59, RX J0501-03, RX J0512-72 and.RX J0515+01. More extensive observations were made for RX Jl313-32 and RX Jll41-64, with Doppler maps derived for RX J1313-32 while the RX J1141-64 spectra show a rise in the spectral slope, indicative of cyclotron radiation. Four ROSAT Bright Survey sources, RBS 0324, RBS 0372, RBS 0490 & RBS 1969, were selected to search for any evidence of them being magnetic cataclysmic variables. More detailed spectroscopy and photometry was obtained for RBS 0324, the only RBS source which shows evidence of being a magnetic system. The other RBS systems are all probably dwarf novae in quiescence.